The Educational Governance of German School Social Science: The Example of Globalization - Szukala, Andrea (JSSE - Journal of Social Science Education, 2016)
Purpose: This article challenges the outsiders' views on European school social science adopting genuine cosmopolitan views, when globalisation is treated in social science classrooms. Method: The article is based on the theoretical framework of educational governance analysis and on qualitative corpus analysis of representative German Laenders' social science curricula from 1994-2014 (n=13). Findings: The article highlights tendencies of renationalisation of the global learning agenda and the problematisation of democracy in contexts of globalisation studies at German schools.